Важливе історико-географічне дослідження - Мицик, Ю. (Історико-географічні дослідження в Україні, 2012)
Рец. на кн. Темушева В.Н. "Гомельская земля в конце XV первой
половине XVI в. Территориальные трансформации в пограничном
регионе". — М.: "Квадрига", 2009. — 190 с. Review of the book: Temushev V.N. "Gomel Land in the Late 15th — the
1st half of the 16th Centuries. Territorial Transformations in the Frontier
Area". — Moscow: "Kvadriga", 2009. — 190 p.